Pengembangan Kawasan Sentra Bisnis sebagai Kawasan TOD dalam Aspek Berjalan Kaki Kelompok Pekerja - Lumban Gaol, Celine Sola Gracia; Permana, Chrisna Trie Hadi (Jurnal Perencanaan dan Pengembangan Kebijakan, 2024)
The Golden Triangle Setiabudi represents an economic zone characterised by significant worker mobility. The congestion resulting from this high mobility can be alleviated by implementing the concept of Transit-Oriented Development at existing transit hubs with development potential, namely Setiabudi Astra Station and Bendungan Hilir Station. To implement this concept effectively, understanding the walking preferences of the worker demographic, particularly those aligned with utilitarian walking profiles, is essential. By discerning these preferences, it becomes possible to identify which transit points can cater to the walking requirements of the worker group. This research is executed through qualitative method with data and information obtained through questionnaire and field observations. This investigation revealed that connectivity and pedestrian infrastructure are pivotal factors influencing the walking preferences of the worker group. Both transit hubs also satisfy the criteria for these variables. Hence, it can be inferred that the areas surrounding Setiabudi Astra Station and Bendungan Hilir Station have met the walking preferences of the working demographic and possess the potential to evolve into Transit-Oriented Development zones. However, there is a need to address indicators that remain unmet, notably the block perimeter length, to offer more diverse walking route options for the worker group.